The Role of Restitution-Based Approach in Promoting Student Responsibility in English Classrooms - Sugirawati Abubakar; Nurdin Noni; Baso Jabu (International Journal of Language, Education, and Literature, 2025)
This study investigates the role of the restitution-based approach in promoting student responsibility in English classrooms at a senior high school in Makassar, Indonesia. The research is grounded in the need for discipline models that foster internal motivation and reflective behavior rather than fear-based compliance. The objective is to explore how restitution principles—namely personal ownership, internal regulation, and behavior restoration—support students in managing their actions within a culturally sensitive context. Using a qualitative case study design, data were collected through classroom observations, interviews with English teachers and eleventh-grade students, and analysis of student reflections. The participants were purposively selected based on their involvement in the restitution-based learning process. The findings reveal that the restitution approach allowed students to correct their behavior voluntarily, admit mistakes without fear of punishment, and express a sense of responsibility through reflective dialogues. Cultural values such as sipakatau (mutual respect) and lempu (honesty) were observed to reinforce the internalization of positive discipline and behavioral accountability. The study concludes that the restitution-based approach is effective in cultivating student responsibility, especially when integrated with local cultural values in the EFL classroom context. It encourages student autonomy, empathy, and initiative—key components for personal and academic growth. It is recommended that English teachers incorporate restorative questioning and student reflection techniques to foster a positive, responsibility-centered classroom environment.